Performance Updating of Concrete Bridges Through Proactive Health Monitoring Methods - Rafiq, Meena Imran; Chryssanthopoulos, Marios K.; Onoufriou, Toula (My University, 2003)
Uncertainties in parameters of any physical model of continuously deteriorating bridges strongly influence management decisions. These uncertainties can be reduced by information obtained through the introduction of health monitoring systems. This paper outlines a Bayesian methodology for performance updating of deteriorating bridges monitored through proactive techniques. The methodology is illustrated with an example of a concrete bridge element subjected to chloride induced deterioration, whereby uncertainties associated with time to corrosion initiation are reduced by the effective integration of monitoring data. This provides a tool to optimise decisions regarding bridge inspection, repair and maintenance activities.
Keywords: Reinforced concrete; Corrosion; Corroded reinforced